Vacuolar-Type H+ -ATPases Are Associated with the Endoplasmic Reticulum and Provacuoles of Root Tip Cells. - Herman, E. M. (1994)
To understand the origin of vacuolar H+ -ATPases (V-ATPases) and their cellular functions, the subcellular location of V-H+ -ATPases was examined immunologically in root cells of oat seedlings. A V-ATPase complex from oat roots consists of a large peripheral sector (V1) that includes the 70-kD (A) catalytic and the 60-kD (B) regulatory subunits. The soluble V1 complex, thought to be synthesized in the cytoplasm, is assembled with the membrane integral sector (V0) at a yet undefined location. In mature cells, V-ATPase subunits A and B, detected in immunoblots with monoclonal antibodies (Mab) (7A5 and 2E7), were associated mainly with vacuolar membranes (20-22% sucrose) fractionated with an isopycnic sucrose gradient. However, in immature root tip cells, which lack large vacuoles, most of the V-ATPase was localized with the endoplasmic reticulum (ER) at 28 to 31% sucrose where a major ER-resident binding protein equilibrated. The peripheral subunits were also associated with membranes at 22% sucrose, at 31 to 34% sucrose (Golgi), and in plasma membranes at 38% sucrose. Immunogold labeling of root tip cells with Mab 2E7 against subunit B showed gold particles decorating the ER as well as numerous small vesicles (0.1-0.3 [mu]m diameter), presumably pro-vacuoles. The immunological detection of the peripheral subunit B on the ER supports a model in which the V1 sector is assembled with the V0 on the ER. These results support the model in which the central vacuolar membrane originates ultimately from the ER. The presence of V-ATPases on several endomembranes indicates that this pump could participate in diverse functional roles.